Peningkatan Kapasitas Kemampuan Guru dalam Proses Pembelajaran dengan Penggunaan Media Pembelajaran berbasis Moodle (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2022)
Education is one aspect that is used as a forum to shape the character of the nation's children. Due to the presence of this pandemic, learning conditions have changed, this is not only happening at the national level but also internationally. The Covid-19 outbreak has forced the government to make policies that must be implemented. This changing learning pattern requires schools to be more adaptive in the changes that occur. Learning continues through online-based learning media or e-Learning which is defined as technology-based learning where learning materials are sent electronically to remote students using computer networks. Therefore, teachers hope and are expected to be able to follow the development of learning media that can be used in the current era. So our current target is SMAN 4 Depok teachers to be able to develop and utilize Moodle-based E-learning learning media. The implementation methods carried out are (1) conducting research on the potential of teachers in partner schools by filling out questionnaires, (2) making guidebooks, (3) Creating Moodle-based Online Learning, (4) training for teachers in partner schools and (5) conducting pretest and posttest in using Moodle. This objective was carried out to increase the capacity of teachers in training using technology and understanding in using Moodle as an alternative learning medium.